Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1128/jb.137.3.1145-1150.1979
|View full text |Cite
|
Sign up to set email alerts
|

Urea: obligate intermediate of pyrimidine-ring catabolism in Rhodosporidium toruloides

Abstract: Urea has been shown to be an obligate intermediate in and the penultimate product of the catabolism of pyrimidine-ring nitrogen in Rhodosporidium toruloides (Rhodotorula). One of a series of mutants selected for its inability to utilize uracil as a sole source of nitrogen was unable to utilize urea also. The mutant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Although we did employ almost identical conditions of growth and enzyme assay, it is possible that the reductive pathway activity was masked by the oxidase activity seen in our strain. Even if catabolism in R. toruloides is initiated by a reduction of uracil to dihydrouracil, previous results (20) have shown that the penultimate step is similar to that of the oxidative pathway. Thus, ambiguity exists regarding pyrimidine-ring catabolism in R. toruloides.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Although we did employ almost identical conditions of growth and enzyme assay, it is possible that the reductive pathway activity was masked by the oxidase activity seen in our strain. Even if catabolism in R. toruloides is initiated by a reduction of uracil to dihydrouracil, previous results (20) have shown that the penultimate step is similar to that of the oxidative pathway. Thus, ambiguity exists regarding pyrimidine-ring catabolism in R. toruloides.…”
mentioning
confidence: 92%
“…Among these only the oxidative pathway, uracil -) barbituric acid --urea + malonic acid -* NH4 + C02, has been substantiated by independent investigations. This catabolic route seems to be limited to a few genera of procaryotes (8,9,11), yet labeled urea is produced from [2-14C]uracil or thymine in both mammalian and fungal systems (2,4,16,17,20). The mechanism for these conversions has not been established.…”
mentioning
confidence: 99%
See 2 more Smart Citations